Why consumers purchase organic products? The role of environment, health and age - Afonso, Carolina (2017)
The market of green products is increasing all over the world, especially in food category that shows a great demand for biologic and organics. The aim of this study is to better understand the why consumers buy organic products, more specifically environmental concern, health consciousness and age The empirical evidence is based on an online survey, using a sample of 279, regular shoppers of organic products in Portugal and Spain. The results show there is a positive relation between environmental concern, health consciousness and green purchase behavior. Environmental concern is stronger than health to explain this relation. Also age is a predictor of green purchase behavior and older consumers with more than 35 years purchase more organics than younger consumers. For managers and marketers, the study enables to develop better marketing strategies to address these consumers and to enhance environmental concern, health and age to foster organics consumption.